Spectral dynamics of pseudo-distributed erbium gain in Raman random fiber laser - Zainol Abidin, N.H.; Lau, K.Y.; Mohd Yusoff, N.; Ng, E.K.; Alresheedi, M.T.; Mahdi, M.A. (Elsevier BV, 2023)
This work explores the spectral dynamics of pseudo-distributed erbium gain in a Raman-based open cavity hybrid random fiber laser (RFL) and compares it to two other schemes; without erbium-doped fiber (EDF) and with EDF integrated mid-cavity. The pseudo-distribution of erbium gain is simulated by splicing short segments of EDF in between single-mode fiber (SMF) spools. The three schemes have similar total SMF lengths of 78 km, and a total of 30 m EDF if any. It was established that the laser wavelength shifts significantly from 1555.936 nm to 1565.904 nm simply by the insertion of EDF mid-cavity, while the distribution of EDF segments along the cavity allowed the generation of dual-wavelength lasing at 1559.964 and 1565.236 nm. The distribution of EDF also generated a higher maximum output power of 485.60 mW compared to the schemes with lumped EDF and without EDF of 409.17 mW and 352.02 mW output powers, respectively. However, the increment came at the expense of a longer instability event from homogenous gain broadening of SBS induced Stokes and a delayed onset of laser threshold condition. We discuss the formations of these different laser schemes and its dynamics permitted solely due to the uniqueness of random fiber lasers. The scheme presents an interesting opportunity in the development of hybrid random fiber lasers, and the analysis of this structure offers insights for better designed dual-wavelength random fiber lasers and the role that rare-earth Erbium dopant plays in the formation of laser in a Raman-based fiber cavity.